2019
DOI: 10.1111/jen.12631
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils as vespid wasp repellents: Implications for their use as a management strategy

Abstract: Recently, plant‐based repellents have been proposed as a potential alternative to classic pesticides against pest wasps, in certain scenarios. Here, the repellent effect of Dysphania multifida essential oil and one of its main terpenoid components, α‐terpinene, were tested under field conditions with natural populations of wasps in Patagonia Argentina. D. multifida essential oil (paico), as well as α‐terpinene, repelled V. germanica wasps in the field. A strong avoidance of food baits treated with the essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…D. multifida (L.) Mosyakin and Clemants, commonly known as “paico”, is an aromatic plant widely used for medicinal purposes, perennial plant of 30–80 cm, pubescent, with a penetrating and pleasant smell, stems numerous, very branchy, leaves small, puberulous-glandulosa, shortly petiolate, with lanceolate or linear lobes, greenish ( Yossen et al, 2019 ).…”
Section: Botanical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. multifida (L.) Mosyakin and Clemants, commonly known as “paico”, is an aromatic plant widely used for medicinal purposes, perennial plant of 30–80 cm, pubescent, with a penetrating and pleasant smell, stems numerous, very branchy, leaves small, puberulous-glandulosa, shortly petiolate, with lanceolate or linear lobes, greenish ( Yossen et al, 2019 ).…”
Section: Botanical Descriptionmentioning
confidence: 99%
“…The majority of the paper identified the components of D. ambrosioides EO are oxygenated monoterpenes. In several studies ( Gupta et al, 2002 ; Boutkhil et al, 2009 ; Brahim et al, 2015 ; Bisht and Kumar, 2019 ), α-terpinene (5) was quantified as the main constituent in D. ambrosioides EO, while ascaridole (29) was reported as the most abundant components in D. multifida EO ( Yossen et al, 2019 ). Less frequently, δ-3-carene (10) , limonene (4) , thymol (20) , carvacrol (19) , γ-terpinene (6) , α-terpinolene (7) , piperitone oxide (31) , geraniol (15) , α-pinene (12) , β-pinene (26) , iso-ascaridole (20) , β-myrcene (1) , α-ocimene (2) , β-ocimene (3) , citronellyl acetate (21) , β-phellandrene (8) , dihydroascaridole (32) , trans -pinocarveol (17) , carvone (24) , piperitone (23) were reported in D. multifida and D. ambrosioides EO ( Arena et al, 2018 ), while p -cymene (9) , and 4-carene (11) were reported as main components of D. ambrosioides EO in another study ( Zefzoufi et al, 2020 ).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Pichi, pine and oregon essential oils were obtained from Hierbas Patagonica SRL (Esquel, Chubut, Argentina). Paico essential oil was obtained from Esquel, Universidad San Juan Bosco, Chubut, as described by (Yossen et al, 2019). Biochemical characteristics are explained in the supplementary material Table S1.…”
Section: Essential Oilsmentioning
confidence: 99%